Cardiac biopsy in childhood. Issue 10 (October 1977) - Mackay, E H; Pickering, D; Littler, W A
Abstract : Endomyocardial biopsy was attempted in 18 children aged 5 months to 15 years with 82% success. Biopsies obtained from 15 children were examined by light and electron microscope making positive morphological diagnoses in 3 cases. The biopsy findings were actively helpful in 7 other cases, which contrasts with experience in adult biopsy series. This is a low risk procedure which does not add to the hazards of cardiac catheterization in children.